The Abstraction Principle and the Separation Principle in German Law - Sadowski, Kornel (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to evaluate the selected principles applied in German law system – the abstraction principle and the separation principle. Presenting the proposed subject the author focus on the obligatory and dispositive legal acts and practical dimensions of the functioning of the selected principles.